COSUTI: A Core Outcome Set (COS) for Interventions for the Treatment of Uncomplicated Urinary Tract Infection (UTI) in Adults - Claire Beecher; Sinead Duane; Akke Vellinga; Andrew W. Murphy; Martin Cormican; Andrew Smyth; Patricia Healy; Michael Moore; Paul Little; Carmel Geoghegan; Declan Devane (MDPI AG, 2022)
Background: Uncomplicated urinary tract infections (UTIs) are among the most common presentations of bacterial infections in the outpatient setting. The variation of outcomes reported in trials to assess the most effective treatment interventions for uncomplicated UTIs has meant that comparing and synthesising the outcomes across trials is challenging and limits the reliability of evidence which would otherwise inform healthcare decisions. Objective: Develop a Core Outcome Set (COS) for interventions for the treatment of uncomplicated UTIs in otherwise healthy adults. Methods: The COS development consisted of three phases: (1) A systematic review to identify outcomes reported in randomised trials and systematic reviews of randomised trials comparing the effectiveness of any interventions for the treatment of uncomplicated UTI in otherwise healthy adults; (2) Outcomes identified in the systematic review were prioritised in an online 3-round modified Delphi survey with healthcare practitioners (n = 68), researchers (n = 5), and people who have experienced or cared for someone experiencing a UTI (n = 180); (3) An online consensus meeting to determine the final COS with healthcare practitioners and policymakers (n = 9), researchers (n = 4), and people who have experienced or cared for someone experiencing a UTI (n = 7). Results: We identified a large number of outcomes. Through the use of robust consensus methods, those outcomes were reduced to a core set of six outcomes that should, at a minimum, be measured and reported in randomised trials and systematic reviews of interventions treating uncomplicated UTIs in adults.